2009
DOI: 10.1080/02640410902998239
|View full text |Cite
|
Sign up to set email alerts
|

The use of individualized speed and intensity thresholds for determining the distance run at high-intensity in professional soccer

Abstract: As with other match analysis systems, ProZone uses an absolute speed threshold to identify running speeds at "high-intensity". In this study, we examined the use of an individualized high-intensity speed threshold based on the speed at the second ventilatory threshold (VT(2speed)) for assessment of the distance run at high-intensity during matches. Ten professional soccer players completed a maximal treadmill test to determine VT(2speed). Match data were identified by means of the ProZone match analysis system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 23 publications
6
158
0
3
Order By: Relevance
“…Whilst the use of absolute speed-zones may provide useful information regarding the performance capacity of players, they do not account for the underlying individual physiological capacity that distinguishes different levels of play. Abt & Lovell (2009) A significant increase in measured peak speed was observed between the ages of U14 and U15 in the present study (P<0.05), with no differences between U12-U14 level, or between U15 to U16 level (P>0.05). These findings are in agreement with Mujika et al (2009), who reported an improved sprint performance between the ages of U14 and U15 (P<0.05), with no further improvement being observed after U15 level (Mujika et al, 2009).…”
Section: Discussionsupporting
confidence: 48%
“…Whilst the use of absolute speed-zones may provide useful information regarding the performance capacity of players, they do not account for the underlying individual physiological capacity that distinguishes different levels of play. Abt & Lovell (2009) A significant increase in measured peak speed was observed between the ages of U14 and U15 in the present study (P<0.05), with no differences between U12-U14 level, or between U15 to U16 level (P>0.05). These findings are in agreement with Mujika et al (2009), who reported an improved sprint performance between the ages of U14 and U15 (P<0.05), with no further improvement being observed after U15 level (Mujika et al, 2009).…”
Section: Discussionsupporting
confidence: 48%
“…The defining of individual speed threshold zones relative to a player's physical capabilities could also be considered for future studies. Male players have been shown to have individual thresholds for high-intensity running, as defined by the speed at the point of the second ventilatory threshold [23]. Accordingly, there is an apparent need to individualise the speed thresholds utilised.…”
Section: Applied Physiology Of Female Soccermentioning
confidence: 99%
“…Accordingly, there is an apparent need to individualise the speed thresholds utilised. Furthermore it has been demonstrated that the use of default thresholds in semi-automated camera systems substantially underestimated the amount of high-intensity running distance completed [23]. Recent research [24] has examined maximum sprinting speed for female soccer players and these values could be used to contribute to a framework of speed threshold classification for female players.…”
mentioning
confidence: 99%
“…For example, thresholds have been reported at velocities of > 8.33 m/s [3], > 7 m/s [10], > 6.39 m/s [1,2], and > 5.83 m/s [9]. there is also a proposal to use an individualized velocity threshold for each athlete [16]. On the other hand, Di Salvo et al [10] suggested analysing sprint activities in a more specific way, classifying them as 'explosive' and 'leading' sprint.…”
Section: Introductionmentioning
confidence: 99%
“…According to Stolen et al [14], players need a period of low intensity activities for lactate re-moval and recovery of lost energy substrates after periods with HIEs during matches. the ability to recover and reproduce performance in subsequent sprints, termed repeated-sprint ability (rSA), is believed to be a specific fitness requirement of soccer and other team sports athletes [15,16].…”
Section: Introductionmentioning
confidence: 99%